KOMPREHENSIF TENTANG HUKUM PIDANA BALASAN DAN IMPLIKASINYA - Lengkong, Lonna Yohanes; Saragi, Paltiada; Sianipar, Andree Washington (Honeste Vivere, 2025)
Retaliatory criminal law is a fundamental paradigm in the criminal justice system that emphasizes appropriate retribution against perpetrators of crimes. This study comprehensively examines the concept of retaliatory criminal law, its implementation in the Indonesian legal system, and its implications. Through a normative juridical approach and comparative analysis, this study reveals that although retaliatory criminal law has strong philosophical legitimacy, its implementation faces various challenges in the context of modern criminal law developments. The New Criminal Code (Law No. 1 of 2023) demonstrates a paradigm shift from pure retribution to a neoclassical approach that integrates corrective, restorative, and rehabilitative elements. This study finds that the implementation of supervisory punishment as an alternative to sentencing reflects the evolution of a more humanistic concept of retaliatory criminal law. However, technical challenges in its implementation, especially for law enforcement officials such as prosecutors, require comprehensive supporting regulations. The study's conclusions demonstrate the need to balance the goal of retribution with aspects of victim recovery and perpetrator rehabilitation to achieve more holistic justice.